2007
DOI: 10.3171/foc-07/12/e8
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Knife stereotactic radiosurgical treatment of idiopathic trigeminal neuralgia: long-term outcome and complications

Abstract: Object Stereotactic radiosurgery (SRS) with the Gamma Knife (GK) is a rapidly emerging surgical modality in the management of medically refractory idiopathic trigeminal neuralgia (TN). The current study examines the long-term outcome in patients with drug-resistant idiopathic TN who underwent GK surgery at the authors‘ institution. Methods One hundred and six consecutive patients (38 men and 68 women) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 34 publications
(77 reference statements)
1
26
0
Order By: Relevance
“…Furthermore, the effect of GKS was found to decrease with time, consistently with previous reports [9,26,[31][32][33] . The actuarial rate of favorable outcome was not affected by any radiosurgical parameters, as reported in previous studies [26,28,32] , and a prolonged period of morbidity ( 1 30 months) was a unique predictive factor for the actuarial rate.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, the effect of GKS was found to decrease with time, consistently with previous reports [9,26,[31][32][33] . The actuarial rate of favorable outcome was not affected by any radiosurgical parameters, as reported in previous studies [26,28,32] , and a prolonged period of morbidity ( 1 30 months) was a unique predictive factor for the actuarial rate.…”
Section: Discussionsupporting
confidence: 79%
“…Park et al, found no significant differences in radiation dose, time to initial response, recurrence or pain relief when GKS was used as a primary or a secondary procedure for idiopathic TN (77). Some studies report higher failure rate when GKS is performed as a secondary procedure (76,78). It was also found to be an effective treatment option for trigeminal neuralgia patients with multiple sclerosis (79), but the study was based on a small group of patients.…”
Section: Open Proceduresmentioning
confidence: 99%
“…A higher integral dose can be augmented either using of two isocenters or using of plugs. Morbidini-Gaffney (Morbidini-Gaffney, 2006) and Alpert (Alpert, 2005) found better pain control using two isocenters, Conversely Flickinger ) in a randomized prospective study found no differences using one or two isocenters and Fountas (Fountas, 2007) reports no differences using one, 2 or 3 isocenters. Nevertheless, nerve dysfunction was more important in the group of patients treated with multiple isocenters.…”
Section: Higher Dose Received By the Brainstemmentioning
confidence: 99%
“…Fountas (Fountas, 2007), reports this phenomenon in 79% of the treated patients. This finding confirms the zone that received the irradiation.…”
Section: Nerve Enhancement After Treatmentmentioning
confidence: 99%
See 1 more Smart Citation